2008
DOI: 10.1177/0886260508317198
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Sexual Abuse Severity Score

Abstract: Childhood sexual abuse (CSA) is common and is associated with both mental and physical health problems in adulthood. Using data from an age and sex-stratified population survey of Olmsted County, MN residents (n=610), we developed a sexual abuse severity score (SASS). The abuse characteristics of 156 CSA respondents were associated with self-reported trauma, somatization, and alcohol use. Characteristics included: age of first sexual abuse, more than one perpetrator, degree of coercion, severity of abuse (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…There is currently no gold standard for the measurement of CSA complexity, although researchers agree that frequency and intensity of abuse, current functioning, and context of CSA matters when attempting to characterize post-abuse adjustment (Casey & Nurius, 2005; Kaysen, Rosen, Bowman, & Resick, 2010; Loeb, Gaines, Wyatt, Zhang, & Liu, 2011; Zink, Klesges, Stevens, & Decker, 2009). Given the evidence demonstrated in the literature, we believe that the CSA complexity is significantly influential in risk for impaired mental health, substance use, and sexual risk taking.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no gold standard for the measurement of CSA complexity, although researchers agree that frequency and intensity of abuse, current functioning, and context of CSA matters when attempting to characterize post-abuse adjustment (Casey & Nurius, 2005; Kaysen, Rosen, Bowman, & Resick, 2010; Loeb, Gaines, Wyatt, Zhang, & Liu, 2011; Zink, Klesges, Stevens, & Decker, 2009). Given the evidence demonstrated in the literature, we believe that the CSA complexity is significantly influential in risk for impaired mental health, substance use, and sexual risk taking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bornstein, Kaplan, and Perry (2007) reported that sexual abuse (mild or severe) was rated as being more traumatic and severe if perpetrated by a parent than by a babysitter. While Zink, Klesges, Stevens, and Decker (2009) found that the factors that contribute to the severity of CSA are the age at first sexual abuse experience, more than one offender, degree of coercion, and the number of occurrences. Based on the previous review the aims of the current study were twofold: (a) to further explore the contribution of coerced, completed penetration and the identity of the offender on the severity of distress (depression and PTS) in adult female survivors of CSA and to (b) examine to what extent the objective circumstances, in terms of the identity of the offender and coerced intercourse, will determine the subjective perception of the CSA experience in terms of severity.…”
Section: Factors Contributing To the Degree Of Negative Outcomesmentioning
confidence: 93%
“…Indicators of CSA severity, drawn from previous research, included (1) genital CSA (Kendler et al, 2000; Zink et al, 2009); (2) vaginal or anal intercourse (Dube et al, 2005; Molnar et al, 2001); (3) younger age of first CSA (Casey & Nurius, 2005; Zink et al, 2009); (4) larger number of perpetrators (Briere & Runtz, 1988; Casey & Nurius, 2005); (5) greater number of CSA occurrences (Jasinki et al, 2000; Zink et al, 2009); (6) longer duration of CSA (Briere & Runtz, 1988; Lange et al, 1999); and (7) physical force or coercion (Dube et al, 2005). …”
Section: Methodsmentioning
confidence: 99%
“…Hughes, Johnson, and Wilsnack (2001) found that lesbians reported more different types of CSA experiences than heterosexual women. Understanding CSA severity is important because the few studies that assessed CSA severity found a “dose-response” relationship between severity (e.g., genital CSA, physical coercion) and adverse outcomes (Bulik, Prescott, & Kendler, 2001; Zink, Klesges, Stevens, & Decker, 2009). …”
mentioning
confidence: 99%
See 1 more Smart Citation